METHODS OF TEACHING ENGLISH TO STUDENTS OF THE NO-PHILOLOGICAL DIRECTION (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
In this article, we will consider different types of methods of teaching English to students of the no philological direction. There is a growing interest in modern methods of teaching English in many parts of the world, and the question arises of how this is to be done – how the curriculum, subject, subject, and methodology should differ from previously developed familiar norms. Much has been written about teaching traditional English, and knowledge of modern methods of teaching English is growing. Many books and articles have been written today to raise awareness of this topic. Innovations and the use of new pedagogical technologies lead to good results.